2014
DOI: 10.1542/peds.2014-1658
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Growth Following Prenatal Lead Exposure and Calcium Intake

Abstract: WHAT'S KNOWN ON THIS SUBJECT:Lead is an ubiquitous environmental pollutant, and no safe threshold for blood lead level in children has been discovered yet. Prenatal lead exposure affects growth of children.WHAT THIS STUDY ADDS: Low level of prenatal lead exposure of ,5.0 mg/dL affects postnatal children' s growth, which was further intensified by low calcium intake. abstract BACKGROUND: The effects on postnatal growth of maternal exposure to low levels of lead during pregnancy have not been well established. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 36 publications
1
31
1
5
Order By: Relevance
“…There are many ways by which lead could directly or indirectly affect bone cell function and then alter children’s height and body composition (Pounds et al 1991). There were some previous studies that performed an analysis similar to ours (Afeiche et al 2011; Hong et al 2014; Schell et al 2009). They performed a prospective analysis looking at lead exposure during pregnancy related to children’s growth.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…There are many ways by which lead could directly or indirectly affect bone cell function and then alter children’s height and body composition (Pounds et al 1991). There were some previous studies that performed an analysis similar to ours (Afeiche et al 2011; Hong et al 2014; Schell et al 2009). They performed a prospective analysis looking at lead exposure during pregnancy related to children’s growth.…”
Section: Discussionmentioning
confidence: 69%
“…In particular, previous investigations identified significant negative correlations between blood lead (BlPb) levels during childhood and child stature and growth over time (Schwartz et al 1986 (United States; blood; range 5 to 35 μg/dL); Vivoli et al 1993 (Italy; blood; mean 7.8 μg/dL); Kafourou et al 1997 (Greece; blood; mean 12.3 μg/dL, sd 8.9); Ballew et al 1999 (United States; blood; mean 3.6 μg/dL); Frisancho and Ryan 1991 (United States; blood; mean 0.5 μmol/L); Cantoral et al 2015 (Mexico; blood; median 0.17 μmol/L); Dallaire et al 2014 (Canada; blood; mean 2.7 μg/dL sd 2.1)). Other studies observed negative associations between lead exposure during pregnancy and children’s height and weight (Schell et al 2009 (New York; blood; mean 2.8 μg/dL, sd 2.63); Afeiche et al 2011 (Mexico; tibia, patella; mean 8.7 μg/g, 10.4 μg/g, sd 9.7, 11.8); Hong et al 2014 (South Korea; blood; mean 1.25 μg/dL sd 1.5)). However, most previous studies focused on postnatal exposures and did not measure exposure to lead during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Afeiche et al (2011) demonstrated that prenatal lead exposure, measured as maternal bone lead, was associated with decreased weight at age 5 years, but only among female children [25]. Prenatal lead exposure, measured in maternal blood, was associated with reduced weight and length Z-scores in offspring at age 2 years participating in the Mothers and Children’s Environmental Health Study [26]. Our findings were restricted to those based on BMI, which may suggest that early life exposure to lead is associated with a weight disproportionate to height, rather than to weight or height alone.…”
Section: Discussionmentioning
confidence: 99%
“…21 The samples of infant-mother dyads were from a myriad of countries including Brazil, 40 Mexico, 16 Iran, 20 , 29 Saudi Arabia, 36 , 39 India, 21 , 30 Tanzania, 31 Poland, 17 Spain, 32 Kuwait, 33 Belgium, 34 China, 19 Argentina, 35 South Korea, 37 and South Eastern Nigeria. 38 Five of the studies 16,17,29,36,37 utilized longitudinal designs to evaluate infant anthropometric growth or developmental outcomes in relationship to maternal lead levels changes throughout pregnancy or to examine cognitive outcomes in infants exposure to Pb 2 + based on umbilical cord blood level samples. For context, when much of the data were collected, the Centers for Disease Control and Prevention (CDC) recommendation was Pb 2 + level 10 μ g/dL or less; however, a Pb 2 + level of 5 μ g/dL or more is considered a level 418 Allen of concern.…”
Section: Summary Of Evidencementioning
confidence: 99%